The convergence of peacebuilding and state building: addressing a common purpose from different perspectives - Jörn Grävingholt; Stefan Gänzle; Sebastian Ziaja (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
Peacebuilding and state building have been discussed in the past as concepts having a difficult relationship with one another, at times involving trade-offs and even dilemmas. Analysing this relationship on the basis of relevant OECD/DAC documents, this briefing paper argues that the two concepts have in fact increasingly converged, representing today two different perspectives on one underlying problem. Regarding their positive vision, their action-guiding principles and even the areas of engagement they suggest, they are now largely congruent. This surprisingly high degree of common ground most likely reflects lesson-drawing from past state-building efforts and the older peacebuilding debate. Consolidating the two strands of the debate into one common framework and moving “from fragility to resilience” could be a logical way forward.
Keywords: 330